Chronic effects of resistance exercise using reciprocal muscle actions on functional and proprioceptive performance of young individuals: randomized controlled trial - Euler Alves Cardoso; Martim Bottaro; Pâmella Rodrigues; Clarice Bacelar Rezende; Thuany Fischer; Jessica Mota; Adailson Fernandes; Rodrigo Luiz Carregaro (Universidade Federal de Santa Catarina, 2014)
Studies have suggested that benefits from resistance exercise (RE) using antagonist muscle pre-activation could be transferred to functional activities. However, chronic studies using pre-activation through reciprocal actions in neuromuscular performance and functional activities are scarce. The aim of this study is to compare the effects of 12 RE sessions using reciprocal muscle actions and a traditional mode on functional and proprioceptive performance of young individuals. Forty eight young subjects were randomized into two groups: 1) reciprocal training (RT, 3 sets; 10 repetitions; knee flexion immediately followed by knee extension), 2) traditional training (TRA, 3 sets. 10 repetitions; knee extension). Pre and post evaluations were characterized by balance tests, hop tests (HT) and "8" shape circuit (RC8). ANOVA 2X2 of mixed model was applied to analyze differences between pre and post-training conditions and between groups. For overall and anterior-posterior balance, no significant differences were found between RT and TRA (p>0.05). Similarly, no post-training differences were found. The medial lateral balance in the dominant limb showed no significant differences in post-training for both groups (p = 0.94), but the non-dominant limb showed significant differences between groups (p<0.01). In HT, significant post-training increases were found within groups (p<0.01), but no differences were found between them (p=0.90). RC8 was different between groups (p=0.03), indicating better post-training running time for TRA. Resistance exercise caused transfers to balance and functional performance, and training with reciprocal muscle actions showed better rates for HT and medial lateral knee balance